Cr(VI) induces ROS-mediated mitochondrial-dependent apoptosis in neuronal cells via the activation of Akt/ERK/AMPK signaling pathway. (June 2020) - Fu, Shih-Chang; Liu, Jui-Ming; Lee, Kuan-I; Tang, Feng-Cheng; Fang, Kai-Min; Yang, Ching-Yao; Su, Chin-Chuan; Chen, Hsin-Hung; Hsu, Ren-Jun; Chen, Ya-Wen
Abstract: Hexavalent chromium (Cr(VI)), a well-known toxic industrial and environmental pollutant, has been shown to cause serious toxic and health effects. However, limited information is available on Cr(VI)-induced neurotoxic potential, with the underlying toxicological mechanisms remain mostly unclear. The present study demonstrated that the mitochondria-dependent apoptosis pathway was involved in Cr(VI)-induced SH-SY5Y cell (the human neuroblastoma cell line) death, which was accompanied by the appearance of cell shrinkage, increased mitochondrial membrane potential (MMP) depolarization and cytochrome c release, and the activation of caspase cascades and poly (ADP-ribose) polymerase (PARP). Cr(VI) treatment also increased the generation of intracellular reactive oxygen species (ROS). Pretreatment of SH-SY5Y cells with antioxidant N- acetylcysteine (NAC) effectively attenuated ROS production and reversed these Cr(VI)-induced cytotoxicity and apoptotic responses. Furthermore, exposure to Cr(VI) significantly increased the phosphorylation levels of Akt, extracellular regulated kinase (ERK)1/2, and AMP-activated protein kinase (AMPK)α. NAC and the pharmacological inhibitor of Akt (LY294002), ERK1/2 (PD980590), and AMPKα (Compound C) markedly abrogated the Cr(VI)-induced activation of Akt, ERK1/2, and AMPKα signal, respectively, with the concomitant inhibition of mitochondrial dysfunction and caspase activation. Additionally, all these inhibitors suppressed Cr(VI)-induced phosphorylation of Akt, ERK1/2, and AMPKα and of each other. Collectively, these results suggest that Cr(VI) exerts its cytotoxicity on neuronal cells by inducing mitochondria-dependent apoptosis through the interdependent activation of Akt, ERK1/2, and AMPKα, which are mainly mediated by ROS generation. Highlights: Hexavalent chromium (Cr(VI)) induced neuronal cell death underwent apoptosis. Cr(VI) triggered ROS-regulated mitochondria-dependent apoptosis in neuronal cell. Akt/ERK/AMPK interdependent activation signal involved in Cr(VI)-induced neurotoxicity.